RELATIONSHIP BETWEEN SOCIAL AND PSYCHOLOGICAL INDICATORS AND THE DIFFICULTY TO ADAPT TO THE STATE OF EMERGENCY OF THE LATVIAN INHABITANTS DURING THE COVID-19 PANDEMIC - Upesleja, Gatis; Perepjolkina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of this study is to investigate relationship between social and psychological indicators and the difficulties to adapt to the state of emergency during the COVID-19 pandemic. Secondary data from the survey (N = 2608, men 39.8%, aged from 18 – 74) carried out in July 2020, in the frame of the National research program (VPP-COVID-2020/1-0011) was used in this study. Data of only some demographic questions (age, gender, education, place of residence, family status, number of children, employment status, and changes in the workload), 6 items as proxy measures of 6 personality traits (persistence, openness, hostility, extraversion, pessimism, and rigidity), Resilience scale, Emotion Regulation Skills Questionnaire (ERSQ-27) and Social Problem-Solving Inventory-Revised version (SPRP-S) as well as answers on a criterion statement: “Overall it was very difficult for me to adapt to the state of emergency” were used. Results showed that it was more difficult to adapt to the state of emergency for such demographic groups as females, persons lining in an urban area, and for those, who have experience changes (in any direction) in their workload. Results of the series of stepwise linear regression analysis showed that Negative problem orientation, Avoidance style of social problem solving, Psychological resilience (negatively), Rigidity and Extraversion are prognostic psychological factors of the difficulties to adapt to lockdown. Based on the results of this study a more targeted recommendations and interventions to enhance the psychological resilience and adaptability to the changes associated with the COVID-19 crisis for the particular groups of the Latvian population could be developed.